Conjugation‐Induced Thermally Activated Delayed Fluorescence (TADF): From Conventional Non‐TADF Units to TADF‐Active Polymers. (4th January 2017) - Wei, Qiang; Kleine, Paul; Karpov, Yevhen; Qiu, Xianping; Komber, Hartmut; Sahre, Karin; Kiriy, Anton; Lygaitis, Ramunas; Lenk, Simone; Reineke, Sebastian; Voit, Brigitte
Abstract : Thermally activated delayed fluorescence (TADF)‐type compounds have great potential as emitter molecules in organic light‐emitting diodes, allowing for electrofluorescence with 100% internal quantum efficiency. In small molecules, TADF is achieved through the formation of intramolecular charge‐transfer states. The only design limitation is the requirement that donor and acceptor entities spatially decouple the highest occupied and lowest unoccupied molecular orbitals, respectively, to minimize exchange splitting. The development of polymeric TADF emitters, on the contrary, has seen comparably small progress and those are typically built up from monomeric units that show promising TADF properties in small molecule studies beforehand. By contrast, herein, a way to achieve TADF properties in cyclic oligomers and polymers composed of non‐TADF building blocks is shown. Due to a strongly decreased energy splitting of the polymer with respect to the individual repeating unit between the lowest singlet and triplet excited state (Δ E ST ) and a sufficiently high radiative decay rate k S r, a highly efficient TADF polymer with up to 71% photoluminescence quantum yield is obtained. For the first time, an encouraging method is provided for producing highly efficient TADF oligomers and polymers from solely non‐TADF units via induced conjugation, opening a new design strategy exclusive for polymers. Abstract : A thermally activated delayed fluorescence (TADF) π‐conjugated cyclic polymer composed of non‐TADF building blocks is developed. Conjugation‐induced highest occupied molecular orbital destabilization leads to a decreased singlet–triplet splitting and efficient TADF in the polymer, while the repeating unit itself shows only inefficient phosphorescence. This conjugation‐induced TADF concept represents a novel molecular design rule particularly for solution‐processable polymeric materials.